Law's environment how the law shapes the places we live - Nagle, John Copeland, 1960-2019. (New Haven, Conn. ; London : Yale University Press, 2010)
John Copeland Nagle shows how our reliance on environmental law affects the natural environment through an examination of five diverse places in the American landscape: Alaska's Adak Island the Susquehanna River; Colton in California's Inland Empire Theodore Roosevelt National Park; and Alamogordo in New Mexico.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Environmental law; Law -- Environmental aspects; Environmental law -- United States -- Case studies; Law; Laws of specific jurisdictions & specific areas of law; Environment law